Sediment classification in the paleo-oceanic environment based on multi-acoustic reflectance characteristics in the Southern Tianshan Mountains - Zhen, Huancheng; Cao, Xinghui; Qu, Zhiguo; Zou, Dapeng; Xiong, Shuai; Song, Jiang; Guo, Hao (Frontiers in Marine Science, 2024)
The grain size of sediments is a crucial parameter in sedimentology, with significant implications for submarine engineering and water conservancy projects. In this study, we developed an acoustic reflection measurement system using a self-developed, high-precision, high-frequency shallow stratigraphic profiler. The system's accuracy was validated with standard acrylic samples. Results showed that within the sediment grain size range of 0.3 to 2.5 mm, the acoustic reflection amplitude increased with grain size. However, distinguishing grain sizes between 0.1 and 0.3 mm from those between 1.0 and 1.5 mm based solely on reflection amplitude proved challenging. Notably, the differences in wavefront flare shapes between these grain sizes were readily apparent. Therefore, combining reflection peak amplitude with time-domain waveform analysis enables more precise sediment grain size classification.